N-(3-Chlorophenyl)-4-nitrobenzenesulfonamide - Chaithanya, U. (International Union of Crystallography, 2012)
There are two independent molecules in the asymmetric unit of the title compound, C(12)H(9)ClN(2)O(4)S, in which the dihedral angles between the planes of the benzene rings are 46.90 (14) and 44.50 (14)°. In the crystal, N—H⋯O hydrogen bonds link the molecules into zigzag chains parallel to the a axis.